Plasmonic Nanobiosensor with Chain Reaction Amplification Mechanism - Recco, Lucas C. [UNESP]; Tokarev, Ihor; Minko, Sergiy; Pedrosa, Valber A. [UNESP] (Wiley-Blackwell, 2014)
Herein we demonstrate a plasmonic nanobiosensor that explores chain reaction amplification mechanisms to transduce chemical signals released in biocatalytic reactions, turning optical signals into a visual spectral range. The sensor has a very simple design: gold nanoparticles resting in the surface of a grafted P2VP film. Changes in the gold nanoparticles' position causes changes in the plasmon coupling mode. This is detected by means of a maximum absorbance shift.
Keywords: biopolymerization; biosensors; nanotechnology; plasmonic platforms; polymerization